08 IL-12/23 directed therapies in SLE. (1st September 2020) - Hahn, Bevra
Abstract : T-cell subsets that promote autoantibody formation and tissue damage play major roles in systemic lupus erythematosus (SLE). Naïve T cells can be driven by interleukin (IL)-12 to Th1 subsets (which secrete interferon gamma [IFNγ) and activate macrophages], and by IL-23 to expand and maintain Th17 subsets (which secrete IL-17A and F and induce chemotaxis). IFNγ-secreting cells and IL-17-secreting cells are found in skin and kidney tissue in patients with active SLE, although not as prominently as cells secreting type 1 IFNs. IL-12 and IL-23 are heterodimers and share a common unit, p40, that binds to the receptor for each cytokine. Ustekinumab is a humanised monoclonal antibody, administered subcutaneously, that binds p40 and thus reduces cell activation by IL-12 and IL-23. It is FDA-approved for use in Crohn's disease, ulcerative colitis, plaque psoriasis and psoriatic arthritis – diseases in which inflammation clearly is driven in part by IL-17. Results were published of an international, multicenter, double-blind, randomised Phase 2 trial in 102 patients with active SLE (excluding active nephritis or CNS or vasculitis) treated with standard care plus ustekinumab or placebo. 1 At 24 weeks of treatment, the primary outcome for ustekinumab was met: SRI-4 response occurred in 62% of the treatment group compared to 33% of the placebo. This 29% difference was highly significant, p=0.006. The BICLA measurement (based on BILAG rather than SLEDAI-2K measures of disease activity) did not show a significant difference between the groups, raising the debate as to which measures are more appropriate for various studies. However, ustekinumab was better than placebo in preventing worsening, as measured by BILAG, and in producing ≥50% improvement in joint counts and CLASI measures of dermatitis. Follow-up studies have shown that the improvement induced by ustekinumab is sustained for 1 to 2 years. Interestingly, clinical improvement was accompanied by a significant drop in gene signature and protein for type 2 IFN (IFNγ), but not type1 IFN. Response rates were similar in patients with high or normal type 1 IFN signatures. These IFNγ data suggest the interference with IL-12 may be more important in SLE than interference with IL-23, and that Th1 cells may be a good therapeutic target. Phase III studies are in progress. Other potential treatments for SLE along this pathway include (1) targeting IL-23p19 (instead of p40) such as guselkumab and tildrakizumab (both FDA-approved for plaque psoriasis), (2) targeting IL17A such as secukinumab and ixekizumab (approved for ankylosing spondylitis, plaque psoriasis and psoriatic arthritis), and 3) anti-IL17R, brodalumab, approved for plaque psoriasis. 2 3 Binding of IL-12 and IL-23 activates JAK/Stat pathways; it is likely that inhibitors such as baricitinib (a Phase II study showed efficacy in SLE), will be effective. In summary, the ustekinumab trial identified a potential new therapy for SLE and suggests that focus on inhibition of IFNγ might be effective in some SLE patients. Learning Objectives: Describe the roles of T-cell subsets in SLE pathogenesis Explain why IL-12 and IL-23 directed therapies are interesting therapeutic targets in SLE Discuss some potential treatments being developed in this area for SLE References: van Vollenhoven RF, Hahn BH, Tsokos GC, et al . Efficacy and safety of ustekinumab, an IL-12 and IL-23 inhibitor, in patients with active systemic lupus erythematosus: results of a multicentre, double-blind, phase 2, randomised, controlled study. The Lancet 2018;392(10155) :1330–39. Sakkas LI, Zafiriou E, Bogdanos DP. Mini Review: New Treatments in Psoriatic Arthritis. Focus on the IL-23/17 Axis. Front Pharmacol 2019;10 :872. Larosa M, Zen M, Gatto M, et al . IL-12 and IL-23/Th17 axis in systemic lupus erythematosus. Exp Biol Med (Maywood) 2019;244(1) :42–51.